Superlight Ambient Temperature Reversible Hydrogen Storage Media Based on Alkali and Alkali Earth Metal-Functionalized 2D Square-Octagon BCN Monolayer - Zhang, Liang (Langmuir : the ACS journal of surfaces and colloids, 2024)
Energy has always been the engine of human beings; however, because of the environmental pollution caused by traditional fossil fuels, the development of more sustainable energy resources is urgently needed. The hydrogen storage medium is essential for its realization. Here, we introduce a hydrogen storage material, a two-dimensional (2D) square-octagon BCN (SO-BCN) monolayer, composed of lightweight elements (B, C, and N) and strategically functionalized with alkali and alkali earth metal atoms (Li, Na, Mg, and K). Notably, LiSO-BCN and Mg@SO-BCN exhibit exceptional reversible hydrogen storage capabilities, surpassing the DOE standard of 5.5 wt %, with gravimetric capacities of 7.129 wt % and an impressive value of 11.656 wt %, alongside low adsorption energies of -0.21 eV/H2 and -0.268 eV/H2 at room temperature, respectively. Our investigation, which combines analysis of the atomic structure, electronic structure, and hydrogen process, reveals distinct mechanisms at play: Li activates the substrate, creating additional adsorption sites on the SO-BCN monolayer. Compared with Li, the functionalization of Mg atoms not only activates SO-BCN via charge transfer but also allows Mg2+ to act as a potent attractor for H2 molecule adsorption. This work provides both promising candidates for future hydrogen storage media based on 2D monolayers and a design paradigm for next-generation hydrogen storage materials, emphasizing the synergy of electron-donating species, substrate activation, and hierarchical porous structures